Low-temperature vacuum permeation of sodium tripolyphosphate and trehalose suppresses the denaturation of myofibrillar proteins in peeled shrimp (Litopenaeus vannamei) during frozen storage - Du, Qi; Fang, Chuangdong; Qi, He; Benjakul, Soottawat; Aubourg, Santiago P.; Zhang, Bin (Frontiers in Nutrition, 2022)
Phosphates and trehalose are widely accepted additives in animal muscle products. In this study, the effects of pre-soaking with sodium tripolyphosphate (STPP) and trehalose under vacuum permeation (VP) conditions on the physicochemical properties of shrimp muscle were evaluated over 120 d of frozen storage. The results indicate the STPP/trehalose-VP treatments significantly reduced the thawing loss and prevented changes in the texture, myofibrillar protein (MP) content, and Ca2+-ATPase activity of shrimp muscle during frozen storage compared with results of control and individual STPP or trehalose soaking treatments. The histological structure analysis revealed the permeated STPP/trehalose distinctly inhibited the dissociation of muscle fibers and reduced physical damage to connective tissues during storage. Furthermore, analysis of the thermal properties indicated STPP/trehalose treatment increased the Tg’ values of shrimp muscle tissues, likely by restricting the mobility of water molecules in muscle tissues and embedding proteins in the glassy matrix. Thus, the physical destruction caused by ice crystal growth was greatly reduced, due to the absence of water molecules around muscle proteins during frozen storage. Accordingly, the combined STPP/trehalose-VP treatment significantly enhanced the stability of frozen shrimp, and the results support the application of traditional cryoprotective additives. The treated shrimp can be stored at comparatively higher temperatures with limited physicochemical reactions during frozen storage.